2015
DOI: 10.5603/fm.2015.0005
|View full text |Cite
|
Sign up to set email alerts
|

The coagulating gland in the male greater cane rat (Thryonomys swinderianus): morphological and immunohistochemical features

Abstract: This study reveals the structure, ultrastructure and immunoexpression of oestrogen alpha and beta receptors (ERa and ERb) (Folia Morphol 2015; 74, 1: 25-32)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…They have showed an extensive expression of ER-α in the nucleus and in the apical bleb or cytoplasm of the secretory epithelium in rat CG. They have indicated that this kind of immunoexpression is not common in all rodents [8]. As reported by Prins and Korach [14], ER-α is basically localized in stroma in the prostate gland of rodents.…”
Section: Review Articlementioning
confidence: 77%
See 4 more Smart Citations
“…They have showed an extensive expression of ER-α in the nucleus and in the apical bleb or cytoplasm of the secretory epithelium in rat CG. They have indicated that this kind of immunoexpression is not common in all rodents [8]. As reported by Prins and Korach [14], ER-α is basically localized in stroma in the prostate gland of rodents.…”
Section: Review Articlementioning
confidence: 77%
“…Plications of the cell membrane are visible at the lateral aspects and the base of the cells [1,9]. Recent ultrastructural and immunohistochemical studies on greater cane rats also indicated the presence of some blebbing on the apical part of the epithelial cells [8]. According to Badia et al, the presence of abundant in-foldings (microvilli) and coated vesicles have been associated with the absorptive activity in the SV.…”
Section: Histological and Histochemical Structure Of Cg: An Updatementioning
confidence: 98%
See 3 more Smart Citations